Unlike a virgin: a meta-analytical review of female mating status in studies of female mate choice. (3rd December 2022) - Richardson, Jon; Zuk, Marlene
Abstract: Studies of female mate choice commonly use virgin females as test subjects, either to control for the effects of mating or because virgin females are presumed to be more responsive to mating cues. Theory predicts that virgin females will be less choosy because they risk dying without mating. Moreover, in many species, females spend more of their lives mated than as virgins. Thus, the exclusive use of virgin females in studies of female mate choice may underestimate the strength or direction of female choice and fail to reflect natural mating decisions. We conducted a systematic meta-analysis of female mate choice studies focusing on three scenarios in which female choice might differ in virgin and mated females: reproductive isolation, inbreeding avoidance, and sexually transmitted disease. Using only virgin females was common (53% of 303 studies). In addition, 38% of studies lacked information on female mating history. Contrary to predictions, we found no evidence that virgin females were less choosy than mated females. Nevertheless, excluding mated females from studies of female mate choice leaves an important gap in our understanding of the role of female preferences in evolution. We therefore encourage future studies of female mate choice to consider the natural context of mate choice and include mated females as test subjects when relevant. Abstract : Studies of female mate choice often use only virgin females. But theory predicts virgins will be less choosy, making such study subjects less than ideal. 53% of 303 studies used only virgin females and only 9% used mated females. However, there was no evidence that virgins females were less choosy. Nevertheless, the lack of studies using mated females leaves an important gap in our understanding of the role of female choice in evolution.